Integrated residence in collective health: interventions for multiprofessional care (Research, Society and Development, 2020)
Objective: to share interventions strategies carried out by a team of residents for multiprofessional care in a Family Health Strategy (FHS). Method: experience report of a resident nurse who is part of a multidisciplinary health team at a public Higher Education Institution, in an ESF in the Municipality of the Western Frontier of Rio Grande do Sul. The experience reported occurred from March 2018 to February 2019 during the practices of a team of first year residents. Results: the strategies include discussion of clinical cases in family health, Nursing records in Primary Health Care (PHC), notification of illnesses and accidents at work in the FHS, shared care schedule in child health care. Conclusion: the different views of the multiprofessional team regarding care conduct add to the provision of qualified care to the user and their family, becoming a space for learning and reflecting on the work process in the FHS.